The impact of monolingual language policy on multilingual identity construction: the case of Saudi Arabia - Alsaawi, Ali (Frontiers in Communication, 2026)
This paper explores the phenomenon of the monolingual language policy in Saudi Arabia and its possible impacts on a minority group—Saudis of Tibetan origin—in constructing a multilingual identity. Language plays a pivotal role in building nations and many countries have a monolingual language policy that views language as symbolic and attached to their peoples' identity and culture, making them skeptical about implementing a multilingual language policy. Minority groups within these countries may encounter challenges in preserving their heritage language and constructing multiple identities that reflect linguistic and cultural differences. Many studies have explored this phenomenon in educational contexts; however, few have done so in social and cultural settings. This study adopted a descriptive single-case study approach to explore the experiences of a Saudi female of Tibetan origin through thematic analysis. The results revealed that the monolingual language policy in Saudi Arabia has an impact on the construction of multilingual identities, with multiple identity construction occurring especially among the first and second generations. The findings indicate the need to explore this phenomenon further with multiple Saudi Tibetans in different age groups to gain more information. It would also be of value to undertake comparative studies with different ethnic groups, as well as examining how multiple identity construction evolves across generations.